Night-restricted feeding of dairy cows modifies daily rhythms of feed intake, milk synthesis and plasma metabolites compared to day-restricted feeding - Salfer, Isaac J. (Br J Nutr, 2020)
The timing of feed intake can alter circadian rhythms of peripheral tissues. Milk synthesis displays a daily rhythm across several species, but the effect of feeding time on these rhythms is poorly characterised. The objective of this experiment was to determine if the time of feed intake modifies the daily patterns of milk synthesis, plasma metabolites, and body temperature in dairy cows. Sixteen lactating Holstein dairy cows were randomly assigned to one of two treatment sequences in a cross-over design with 17 d periods. Treatments included day-restricted feeding (DRF; feed available from 0700 to 2300 h) and night-restricted feeding (NRF; feed available from 1900 to 1100 h. Cows were milked every 6 h on the last 7 d of each period and blood samples were collected to represent every 4 h over the day. Peak milk yield was shifted from morning in DRF to evening in NRF, while milk fat, protein, and lactose concentration peaked in the evening in DRF and the morning in NRF. Plasma glucose, insulin, NEFA, and PUN fit daily rhythms in all treatments. Night-feeding increased the amplitude of glucose, insulin, and NEFA rhythms and shifted the daily rhythms by 8 to 12 h (P < 0.05). Night feeding also phase delayed the rhythm of core body temperature and DRF increased its amplitude. Altering the time of feed availability shifts the daily rhythms of milk synthesis and plasma hormone and metabolite concentrations and body temperature, suggesting that these rhythms may be entrained by food intake.